Konsep Terapi Salat Menurut Perspektif Moh. Ali Aziz - Sopyan Hadi Budiman; Cucu Setiawan; Yumna Yumna (Jurnal Penelitian Ilmu Ushuluddin, 2022)
Prayer is a work that is intended to worship based on predetermined conditions that begin with takbiratul ihram and end with greetings. Prayer is one of the commands from Allah that must be done by a Muslim. Prayer in addition to being an obligation, can be used as a therapy. Prayer therapy is a therapy that takes the essence of prayer and reading in prayer. These points come from the readings in the six prayer movements viz. Standing, Bowing, I'tidal, Prostration, Sitting between the two prostrations and Tasyahud at the beginning and at the end. The purpose of this study is to describe the views of Moh. Ali Aziz on the concept of prayer therapy. This research is a research that uses a qualitative method using a literature study. The analytical method used is descriptive content analysis technique. The results of this study show the happy prayer therapy written by Moh. Ali Aziz is a therapy by performing prayers and contemplating the points contained in the prayer movement which consists of standing, bowing, I'tidal, prostration, sitting between two prostrations and tasyahud. The results of happy prayer therapy can bring a servant closer to his Lord, and can get rid of all negative thoughts and turn them into positive thoughts so as to create peace of mind and happiness. The results of this study are very useful for someone who is experiencing problems or is not happy. The conclusion of this study is to invite all Muslims to contemplate and pray solemnly by contemplating the important points contained in each prayer movement.